دراسة تجريبية تحليلية لظاهرة الامتصاصية في مركبات البولي استرغير المشبع– بودرة الخشب - منصور رامي; الحموي لطيفة (Latakia University Journal -Engineering Sciences Series, 2017)
يهدف هذا البحث إلى دراسة سلوك امتصاص الماء في المواد المركبة المؤلفة من البولي استر غير المشبع /نفايات بودرة الخشب .لتحقيق هذا الهدف تم تحضير عينات بطريقة الكبس بنسب مختلفة لمادة الأساس الرابطة البوليميرية مع النفايات العضوية الناتجة عن ورش النجارة (بودرة الخشب ).تم قياس كثافة الألواح المصنعة وبينت نتائج الكثافة إمكانية الحصول على ألواح خشب صناعي من النوع القاسي .تم إجراء التجارب العملية من اجل تحديد النسبة المئوية لامتصاص الماء ,حيث تم إجراء اختبار الامتصاصية على العينات المقتطعة وغمرها في الماء العذب غير المقطر ,وحساب الوزن المكتسب للعينات والانتباج الحاصل من اجل معرفة التغيرات النهائية في المنتج , ومن خلال هذه الدراسة تبين زيادة الامتصاصية مع زيادة نسبة المالئ العضوي وازدياد حجم الحبيبات ,وان سلوك الامتصاص يخضع لقانون فيك Fick للانتشار في اغلب العينات .وتم حساب معامل الانتشار D و البارامترات المعبرة عن عملية الانتشار ورسم المخططات البيانية المرافقة لنتائج الامتصاصية .وأظهرت النتائج إمكانية تصنيع ألواح من الخشب الصناعي دون الحاجة إلى المعالجة المسبقة لبودرة الخشب. In this study, we have investigated the water absorption behavior of unsaturated polyester /wood flour wastes composites materials. To achieve that, specimens were prepared by using compressing method with different ratio of polymer matrix with organic wastes produced from carpentry workshop (wood flour).Density of produced panels has been measured and the obtained results showed that there is an ability to produce hardindustrial wood panels. Practical experiments had been achieved to determine the percentages of water absorption. Absorption test was achieved on the cut specimens by immersing them in natural water (un-distilled) and measuring the gained weight of specimens and the resulted swelling to determine the final changes in the product. Through this study, we find that the absorbability has increased with the increment of organic filler ratio and the practices sizes increment. In addition, we also find that the absorption behavior follow Fickian law of diffusion in most specimens. We calculated the diffusion coefficient D and other parameters of diffusion process and we also plotted the associated plotsof the absorbability results. The obtained results showed that there is an ability to produce planes of industrial wood without any pretreatment of wood flour.